Interpretation on Groundwater Hydro-Chemistry in West Coastal Locations of Kanyakumari District, India - Anantha Krishnan, E.; Ganesan, K.; Shobana, Sutha; Dharmaraja, J.; Narayan, S.A. (Asian Journal of Chemistry, 2015)
In the present investigation, groundwater sampling and characteristics were carried out by collecting 19 samples from 19 different stations (S1-S19) of west coastal locations in between Kanyakumari to Thengapatnam, during the period August 2012 to August 2013 to decipher the hydro-geochemistry, hydro-chemical parameters with facies by using Chadha's plot and the analytical data were interpreted according to published guide line. The results illustrate that there is a great correlation between electrical conductivity and total dissolved solids. pH was within the maximum limit as per ALFA i.e., 7.6 to 8.7. Further, all the study locations revealed that the area up to a distance of 224-273 m was found to be brackish to saline in nature. Mainstream of the samples exist in less same way with minor exceptions irrespective of type of weather and are within the limit approved by WHO.